Do agricultural support and cash transfer programmes improve nutritional status?. (26th November 2021) - Gitter, Seth R.; Manley, James; Bernstein, Jill; Winters, Paul
Abstract: Agricultural support and cash transfer programmes are both used to improve nutrition outcomes in developing countries. Our review of both programmes based on a literature search of over 22 000 articles in 8 databases has four key findings. First, these programmes often increase total food consumption, but half of agricultural programmes do not measure changes in total food consumption; (2) over 20% of cash transfer programmes fail to improve the quantity of food consumed, though (3) both programme types improved the quality of food consumption. Finally, (4) both programme types show weak evidence of improvements in micronutrients and anthropometric outcomes.